Devolution, regionalism, and regional development the UK experience (Routledge, 2008)
Written by academics from the fields of geography, economics, town planning, public policy, management, public administration, politics and sociology, this book provides an overview and critical perspective on the impact of devolution on regionalism in the UK since the late 1990s.